(untitled) (Tempo e Argumento, 2022)
The present study aims to understand the roots of the current uses of Ritalin (methylphenidate) and how the explanations about neural backgrounds for mental disorders make the use of drugs acceptable and even desirable to “treat” behavioral problems and enhance academic performance. We discuss the Attention Deficit Hyperactivity Disorder (ADHA) diagnosis, which allowed the use of methylphenidate and other stimulants in children; how the drug was used over time, since entering the market in the 1950s; the role of the biological explanations about the brain in emergence of ADHD as a psychiatric diagnosis treatable with drugs; and how these issues result in prescribing and using methylphenidate to enhance cognitive performance. Finally, we argue that the beliefs in neural background to mental disorders may create relevant social consequences: the relativization of social issues related to suffering; a tendency of trying to prevent “threats” through treatment and stigmatization of individuals considered in risk for mental distress; physical and neural damages due to exceeded and/or long-term use of psychoactive drugs, among others.